Effect of low-dose aspirin on the development of ovarian hyperstimulation syndrome and outcomes of assisted reproductive techniques in the women with PCOS, a randomized double-blinded clinical trial - Bahia Namavar Jahromi; Jaleh Zolghadri; Elham Rahmani; Shohreh Alipour; Zahra Anvar; Afsun Zarei; Pegah Keramati (Elsevier, 2019)
Objective: Ovarian hyperstimulation syndrome (OHSS) is a major complication of assisted reproductive technologies (ART). Polycystic ovary syndrome (PCOS) is a risk factor for OHSS. The aim of this randomized clinical trial (RCT) was to study the effect of low-dose aspirin (LDA) on the development of OHSS and ART outcomes in PCOS during ART. Materials and methods: This double-blinded placebo controlled RCT was performed on 232 PCOS infertile women in their first ART cycles during 2010-2016. LDA and placebo capsules were prepared, packed and specified by code numbers in similar shapes. One package was given to every woman and asked to take one capsule/day since the 21st day of her cycle prior to the gonadotropin stimulation. Gonadotropin releasing hormone agonist long protocol and triggering by human chorionic gonadotropin were used. Development of moderate to severe OHSS and their ART outcomes were documented then the codes were broken and data analyzed. Chi-square and Mann-Whitney U tests were used for the statistical analyses. Results: Eighteen cases that did not follow the study design were excluded. 214 cycles remained for the final analyses with 109 cases in LDA and 105 in the placebo group. Rate of the moderate to severe OHSS in LDA group was 34.9% compared to 30.5% in placebo group (P = 0.494). Fertilization rate was 71.8% vs 65.1% (P = <0.001) and the mean number of grade III embryos were 3.28 ± 3.53 vs 1.46 ± 1.42 (P = 0.014) in LDA and placebo groups, respectively. The mean number of the oocytes in different grades, total and frozen embryos also implantation and clinical pregnancy rates were not different between the groups. Conclusion: Moderate to Severe OHSS was not decreased but fertilization rate and the mean number of poor quality embryos were increased in LDA arm. Registration number: IRCT 201105216541N1. Keywords: Ovarian hyperstimulation syndrome, Assisted reproductive technology, Polycystic ovary syndrome, Aspirin, Infertility, Fertilization